PENYELIDIKAN GEOLOGI TEKNIK UNTUK PENENTUAN LOKASI PEMBANGUNAN AS BENDUNGAN PELOSIKA DI DESA ASINUA JAYA, KECAMATAN ASINUA, KABUPATEN KONAWE, PROVINSI SULAWESI TENGGARA - Sawung Kawedar Daya Kristy; Hadi Nugroho; Wahju Krisna Hidajat; Dandung Marhento (Geological Engineering E-Journal, 2014)
Development plan of Dam Pelosika is located in a river Konaweha, Asinua Jaya village, Asinua District, Konawe, Southeast  Sulawesi  Province. Konaweha river has a length of 127 km and has an Regional water bin area of 6,664 km2.The purpose of this research is to study the geology around the River Konaweha to determine the condition of the morphology and lithology of the area so it can be recommended as dam Pelosika construction site of several alternative locations. Then determine the engineering geology condition of the selected location. In addition, determine the spread and water level inundation. The research method used was a descriptive survey method engineering geological mapping. The descriptive method is collecting secondary data from topographic maps, regional geological maps, earth maps and technical data of dams. While the analytical survey method is analyze the data based on the geological conditions of the regional geology and geological engineering investigation of the data included surface geological conditions, core drilling and test results of geoelectric. Based on investigation in the field, the morphological conditions of the studyis divided into three units namely structural denudated steep hills landform unit, denudated structural undulating hills landform unit and plains of fluviall and denudated form unit. The lithology of the study area is a constituent of metamorphic rocks such as schist of Paleozoic Metamorphic Formation, conglomerates and sandstones of Pleistocene age Alangga Formation and deposition of clay to gravel-sized Alluvium Holocene age. Based on several parameters geology and geological engineering, so that from several alternative locations as dam development determined that 4th alternative locations is a selected location for construction Dam Pelosika. The foundation of the dam on the left side at elevation +121 m rests on weathering soil bedrock sandy silt-sized. The foundation of the center of the dam at elevation +16.9 m rests on clay silt layers firm. The foundation of the right of the dam at elevation +115 m rests on weathering soil bedrock sandy silt-sized. The inundation spread area is 165.98 km2, constrained by the topography of the area around the river. Inundation water levels is +180 m.